2022
DOI: 10.1002/brb3.2817
|View full text |Cite
|
Sign up to set email alerts
|

A postpartum enriched environment rescues impaired cognition and oxidative markers in aged mice with gestational inflammation

Abstract: Introduction Previous studies have shown that gestational inflammation can accelerate age‐associated cognitive decline (AACD) in maternal mice; enriched environments (EEs) have been reported to protect normally aging mice from AACD and improve mitochondrial function. However, it is unclear whether the nitrosative stress‐related proteins tet methylcytosine dioxygenase 1 (TET1) and S‐nitrosoglutathione reductase (GSNOR) are involved in the accelerated aging process of gestational inflammation and whether EEs can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, these inflammatory mediators can reduce the expression of tight junction proteins such as occulin and claudin-5, destroy the integrity of blood-brain barrier, and enter the brain to activate adaptive immune cells, leading to brain immune instability ( 31 ). In animal experiments, injecting LPS into the abdominal cavity of mice can lead to learning and memory impairment by increasing the permeability of the blood-brain barrier, and the permeability of the blood-brain barrier will recover after rebuilding the balance of gut microbiota ( 32 ). It has been reported that after oral supplementation of intestinal prebiotics, the number of probiotics such as lactobacillus and bifidobacterium in the intestine of PND mice increased, the level of inflammatory factors in the hippocampus decreased, and the cognitive function improved ( 33 ).…”
Section: Gut Microbiota and Central Nervous Inflammatory Responsementioning
confidence: 99%
“…Meanwhile, these inflammatory mediators can reduce the expression of tight junction proteins such as occulin and claudin-5, destroy the integrity of blood-brain barrier, and enter the brain to activate adaptive immune cells, leading to brain immune instability ( 31 ). In animal experiments, injecting LPS into the abdominal cavity of mice can lead to learning and memory impairment by increasing the permeability of the blood-brain barrier, and the permeability of the blood-brain barrier will recover after rebuilding the balance of gut microbiota ( 32 ). It has been reported that after oral supplementation of intestinal prebiotics, the number of probiotics such as lactobacillus and bifidobacterium in the intestine of PND mice increased, the level of inflammatory factors in the hippocampus decreased, and the cognitive function improved ( 33 ).…”
Section: Gut Microbiota and Central Nervous Inflammatory Responsementioning
confidence: 99%